Characterization and genetic diversity of Xanthomonas campestris pv. campestris causing black rot disease in crucifers in North India - and RICHA RAGHUWANSHI, PRIYANKA SINGH RATHAUR, DINESH SINGH* (Indian Phytopathology, 2016)
Forty seven isolates of Xanthomonas campestris pv campestris (Xcc) were isolated from different crucifers growing in northern parts of India for characterization and genetic diversity study. All the isolates were gram negative rod, aerobic with monotrichous flagella and produces yellow, translucent, raised colonies on NSA medium. The isolates were further confirmed by amplifying hrp F gene.Natural incidence of black rot disease in Indian mustard, vegetable mustard, radish and turnip crops in field was found quite low (2-15%), whereas in cole crops including cauliflower, cabbage, broccoli and knol khol, the incidence was 10 to 40 per cent. Repetitive DNA polymerase chain reaction-based fingerprinting (repPCR) using BOX primers was done to assess the genetic diversity of these Xcc isolates along with three out group bacteria, X. oryzae pv. oryzae Xoo-4, X. citri pv. citri Xac-63 and Bacillus subtilisDTBS-5. Cluster analysis of fingerprinting of BOXPCR clearly separated isolates of Xcc from out group bacteria and formed eight diverse groups or DNA types. Maximum isolates clustered in DNA type 2 (15 isolates) followed by DNA type 6 (8 isolates) and DNA type 1 (7 isolates). The Jaccard’s similarity coefficient matrix values ranged from 0.76 to 0.17, which indicates high level of genetic diversity among Xcc isolates.